(3MGTjI GdeYGdes - (3GdHgHgGfj, GdCUagGfj, GdaGQSj, eMeO HGbQ Hf eMeO Cced GdhMjO, J (B1205(3g`s ((3bGSe Hf eMeO MSf TeSGs)
(3ChdgG (B:s
(3hHdG aYGd(B. (3f bdJ aj LedI GdCaYGd aYd GdeYUhe hgh MLI cbhdg(B: (3hGdYde Hg aj GdCMcGe GdTQYjI(B...s
(3BNQgG (B:s
(3hGdVQhQGJ JHjM GdeMXhQGJ dG ZjQgG (B...(3EPG bGd Cf GdTjA cPG adGHO ef GdMce HYOe chfg dc ef GdKHhJ aj GdTQY HdG THgI(B... (3eKd GdehbJ djS dc hhLgg hGVM(B. (3JeJ GdMGTjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3, U(B154s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B350s
(3eYLe GdeDdajf(B:(3L(B3(3, U(B154s
(3GdPQjYI, Qbe(B: 1136s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis